Penguatan Self-Regulated Learning Mahasiswa melalui Pembelajaran IPA Berbasis Nilai-Nilai Islam pada Mata Kuliah Materi dan Energi - Ledang, Irwan; Asshagab, Siti Mutiaraningsih (LP2M IAIN Ambon, 2025)
This study analyzes the development of students’ self-regulated learning in Science Education (IPA) based on Islamic values in the Materials and Energy course. This qualitative descriptive research involved eight second-semester students of the Tadris IPA Study Program at IAIN Ambon. Data were collected through in-depth interviews, participatory observations, and students’ learning reflections, and analyzed using the Miles and Huberman model. The findings reveal that Islamic values such as gratitude (syukur), trustworthiness (amanah), and discipline play a significant role in strengthening students’ self-regulation learning across three learning phases: forethought (intention and goal setting), performance control (time and strategy management), and self-reflection (spiritual evaluation of learning outcomes). The application of these values enhanced students’ intrinsic motivation, independence, and scientific responsibility. Overall, Islamic values-based science learning effectively fosters reflective, independent, and religious scientific character grounded in spiritual awareness.